2008
DOI: 10.1038/mt.2008.1
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial of Autologous Ascites-derived Exosomes Combined With GM-CSF for Colorectal Cancer

Abstract: Exosomes are small membrane vesicles that are secreted by a multitude of cell types. The exosomes derived from dendritic cells (Dex), tumor cells (Tex), and malignant effusions demonstrate immunomodulatory functions, and are even under clinical trial for cancer treatments. In this study we report the phase I clinical trial of the ascites-derived exosomes (Aex) in combination with the granulocyte-macrophage colony-stimulating factor (GM-CSF) in the immunotherapy of colorectal cancer (CRC). The Aex isolated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
445
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 673 publications
(471 citation statements)
references
References 43 publications
4
445
0
4
Order By: Relevance
“…It has been shown that GM-CSF promotes bone metastasis of breast tumors [29,30] and expansion of MDSC in melanoma patients [31]. Although in tumor models where MDSC do not appear to be the major suppressor cells, GM-CSF has been shown to be a potent inducer of anti-tumor immune responses [32]. On the other hand, gamma chain cytokines IL-7 and IL-15 have been shown to play a critical role in augmenting anti-tumor activity of T cells [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GM-CSF promotes bone metastasis of breast tumors [29,30] and expansion of MDSC in melanoma patients [31]. Although in tumor models where MDSC do not appear to be the major suppressor cells, GM-CSF has been shown to be a potent inducer of anti-tumor immune responses [32]. On the other hand, gamma chain cytokines IL-7 and IL-15 have been shown to play a critical role in augmenting anti-tumor activity of T cells [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…52 -665+ days post-vaccination survival was recorded in patients; MAGE-specific T cell response was observed in 1 out of 3 patients and lytic activity of NK cells was reinstated in 2 out of 4 patients. Another Phase I clinical trial in 40 patients with advanced colorectal cancer (stage III/IV) was initiated using ascites-derived exosome (Aex) with or without granulocytemacrophage colony-stimulating factor (GM-CSF) [187]. Both vaccination regimens were welltolerated by patients with some counts of grade 1-2 adverse effects were noted including reaction at injection site, nausea, pain, fever and fatigue.…”
Section: Clinical Trials and The Future Of Exosome Therapeuticsmentioning
confidence: 98%
“…Similar to DCs, DC-derived exosomes bearing MHC-I complexed with tumour-derived peptides were found to activate T and/or B cells to induce anti-tumour immune responses [17,77,101,102]. To test the potential for exosomes to be used as cell-free vaccines against cancers, DC-derived exosomes have undergone phase I trial and are currently in phase II trial [12,103105]. In addition to MHC-bound antigens expressed on the exosomal surface, mature DC-derived exosomes also show surface expression of ICAM-1, which is important for the induction of immune responses, such as T-cell activation [106], and the NKG2D ligand, which is a TNF superfamily ligand that binds directly to NK cells to induce their activation/proliferation and cause an anti-tumour immune response [107,108].…”
Section: Therapeutic Applications Of Surface-modified Evsmentioning
confidence: 99%
“…Therefore, gaining a better understanding of the heterogeneity and molecular composition of EVs could allow us to determine more suitable subpopulations for certain EV-based therapeutics (i.e., by identifying subpopulations that can exert particular effects without unwanted side-effects). The vesicle doses have varied across the existing studies, ranging from 1 to 500 μg per in vivo injection [12,104,105,149151], further emphasizing that the heterogeneity of EVs needs to be characterized to avoid the induction of adverse effects in patients. Although some methods have been developed to detect EV heterogeneity, their detection sensitivities and specificities must be improved to enable researchers to precisely characterize each subpopulation and the compositions of individual vesicles.…”
Section: Limitations and Factors That Should Be Overcome For The Thermentioning
confidence: 99%